A Whole-Food Plant-Based Diet Reversed Angina without Medications or Procedures. (10th February 2015) - Massera, Daniele; Zaman, Tarique; Farren, Grace E.; Ostfeld, Robert J.
Abstract : A 60-year-old man presented with typical angina and had a positive stress test. He declined both drug therapy and invasive testing. Instead, he chose to adopt a whole-food plant-based diet, which consisted primarily of vegetables, fruits, whole grains, potatoes, beans, legumes, and nuts. His symptoms improved rapidly, as well as his weight, blood pressure, and cholesterol levels. Plant-based diets have been associated with improved plasma lipids, diabetes control, coronary artery disease and with a reduction in mortality. Adoption of this form of lifestyle therapy should be among the first recommendations for patients with atherosclerosis.